2018
DOI: 10.1371/journal.pone.0198397
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic ability of inner macular layers to discriminate early glaucomatous eyes using vertical and horizontal B-scan posterior pole protocols

Abstract: PurposeTo evaluate the diagnostic ability of macular ganglion cell (mGCL) and macular retinal nerve fiber (mRNFL) layers, to detect early glaucomatous eyes, using the new segmentation software of Spectralis optical coherence tomography (OCT) device (Heidelberg Engineering).MethodsA total of 83 eyes from 83 subjects were included in this observational, prospective cross-sectional study: 43 healthy controls and 40 early primary open-angle glaucoma (POAG) patients. All participants were examined using the Horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Note, the preset scan pattern with the highest number of B-scans produces a much lower automatic real time mean function and significantly lower image quality, and hence was not used. The difference in horizontal versus vertical B-scan resolution has been shown not to have a significant impact on thickness outcomes 33 . Scans with significant artefacts or signal strength of lower than 15 dB were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Note, the preset scan pattern with the highest number of B-scans produces a much lower automatic real time mean function and significantly lower image quality, and hence was not used. The difference in horizontal versus vertical B-scan resolution has been shown not to have a significant impact on thickness outcomes 33 . Scans with significant artefacts or signal strength of lower than 15 dB were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing the pRNFL thickness measured with horizontal and vertical scans, the horizontal sectors show better agreement compared to the vertical sectors in both scan setting (1 and 2). Comparison of macular thickness measurements with horizontal and vertical scan directions has been reported previously [ 19 , 27 , 28 ]. To our knowledge, this is the first study that compared the influence of different scan directions on the pRNFL measurements.…”
Section: Discussionmentioning
confidence: 93%
“…75,76,344,416 The diagnostic ability of individual or combined layer measurements derived from Spectralis OCT has been explored in recent investigations. The GCL 31,65,90,243,253,295 , GCC, 65,192 and mRNFL 68 thickness were found to be the single best parameter for detection of glaucoma in different studies; however, no consistent difference has been observed between macular outcomes of interest. Inner macular thickness measurements on larger grids 65 or outer sectors 31,68,243,295 have displayed better diagnostic capability for early and preperimetric glaucoma.…”
Section: C Detection Of Preperimetric and Perimetric Glaucoma With Macular Oct Imagingmentioning
confidence: 92%
“…The GCL 31,65,90,243,253,295 , GCC, 65,192 and mRNFL 68 thickness were found to be the single best parameter for detection of glaucoma in different studies; however, no consistent difference has been observed between macular outcomes of interest. Inner macular thickness measurements on larger grids 65 or outer sectors 31,68,243,295 have displayed better diagnostic capability for early and preperimetric glaucoma. Also, temporal 31,295 or temporal and inferior 68,90 macular sectors have generally performed better for this task.…”
Section: C Detection Of Preperimetric and Perimetric Glaucoma With Macular Oct Imagingmentioning
confidence: 92%
See 1 more Smart Citation